(untitled) (Journal of School Administration Research and Development, 2016)
An important aspect of school leadership is relationship development, but developing meaningful relationships as a school leader is challenging. School leader relationships are challenged by diverse stakeholder groups, varied contexts, and difficult situations. The complex nature of school leader relationships necessitates explicit training for leaders on relational skills. The purpose of this paper is to provide professional development recommendations for school leaders regarding three aspects of relationships: rapport, trust, and communication. Specific ideas for school leaders regarding how to establish rapport, trust, and effective communication are discussed. Finally, the use of structured role-play is discussed as the recommended approach to professional development for school leader relationships.